2017
DOI: 10.3389/fpsyg.2017.01006
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s Autonomy Support and Engagement in Math: Multiple Mediating Roles of Self-efficacy, Intrinsic Value, and Boredom

Abstract: Previous studies have highlighted the impacts of environmental factors (teacher’s autonomy support) and individual factors (self-efficacy, intrinsic value, and boredom) on academic engagement. This study aimed to investigate these variables and examine the relations among them. Three structural equation models tested the multiple mediational roles of self-efficacy, intrinsic value, and boredom in the relation between teacher’s autonomy support and behavioral, emotional, and cognitive engagement, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 51 publications
6
35
1
1
Order By: Relevance
“…Previous studies have also confirmed that students' self-efficacy plays a mediating role between teachers' behaviors and their learning performance. In a study by Wang et al (2017) with 637 Chinese middle school students, selfefficacy had a mediating effect between TAS and learning engagement in math. Considering the above findings, this study proposed the following hypothesis.…”
Section: Mediating Effects Of Self-efficacymentioning
confidence: 98%
“…Previous studies have also confirmed that students' self-efficacy plays a mediating role between teachers' behaviors and their learning performance. In a study by Wang et al (2017) with 637 Chinese middle school students, selfefficacy had a mediating effect between TAS and learning engagement in math. Considering the above findings, this study proposed the following hypothesis.…”
Section: Mediating Effects Of Self-efficacymentioning
confidence: 98%
“…Subjective values refer to the individual significance of achievement-related activities and outcomes (e.g., intrinsic value, which refers to the students’ beliefs about the learning activity itself). The effects of perceived teachers’ autonomy support on students’ self-efficacy and intrinsic value have been empirically assessed in different educational settings [ 61 , 62 , 63 , 64 , 65 ]. The findings indicated that autonomy-supportive teaching increases self-efficacy and intrinsic value.…”
Section: Methodsmentioning
confidence: 99%
“…Students who intrinsically value academic tasks are motivated to put forth more effort and show greater persistence and enjoyment in academic activities (Eccles, 1983;Eccles and Wigfield, 2002;Spinath et al, 2006;Wigfield and Cambria, 2010;Federici and Skaalvik, 2014). Wang et al (2017) found that Chinese middle-school students with higher intrinsic value tended to be more engaged in mathematics. In summary, drawing on perspectives and empirical evidence based on implicit theory, we hypothesized that intrinsic value would mediate the association between implicit theory and academic engagement among students.…”
Section: Intrinsic Value As a Mediatormentioning
confidence: 99%